Efforts to Support Public Interest in Visiting Percut Water Park to Improve the Economy of the Percut Sei Tuan Community - Desi Yanti Ritonga; Fauzi Arif Lubis (Britain International for Academic Research (BIAR) Publisher, 2025)
The tourism industry today is part of the creative industry or creative economy that can be relied on to boost the nation's economy. This study aims to determine the effect of attractiveness, accessibility/location, rates/prices, facilities, and information on interest in visiting Taman Air Percut. This study uses a quantitative research methodology. The conclusion of the results of this study is the results of testing conducted using SPSS regarding the partial effect of variable X on Interest in Visiting obtained The variable of the attractiveness of tourism products (X1) has a tcount value> ttable, this indicates that the attractiveness of tourism products (X1) has a partial effect on Interest in Visiting (Y) at Taman Air Percut. The variable of accessibility/location (X2) has a tcount value> ttable which means Ha2 is accepted this indicates that accessibility/location (X2) has a partial effect on Interest in Visiting (Y) at Taman Air Percut. The variable of rates/prices (X3) has a tcount value <ttable which means Ha2 is accepted this indicates that rates/prices (X3) have a partial effect on Interest in Visiting (Y) at Taman Air Percut. The Facility variable (X4) has a tcount value > ttable, this shows that the Facility (X4) has a partial effect on the Interest in Visiting (Y) at Percut Water Park. The information variable (X5) has a tcount value > ttable, which means that Ha2 is accepted, this shows that information (X5) has little impact on the presence of Percut Water Park (Y).